Analiza opłacalności wykorzystania energii słońca i wiatru dla budynku jednorodzinnego = The analysis of the economic viability of wind and solar energy use for a detached family house - Słobodzian-Ksenicz, Oryna; Jasiewicz, Marzena; Nadolna, Marzena; Szarszewski, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The current project costs of wind and solar energy use have been compared with traditional power sources and the economic viability of the investment has been estimated. The most economically viable investment is a wind power plant but it does not guarantee a continuous energy supply throughout the year. Therefore a hybrid plant has been proposed as an investment economically viable.
Keywords: budynek jednorodzinny; energia słońca; energia wiatru; opłacalność; single-family building; sun energy; wind energy; cost-effectiveness